Teachers need socio-moral competencies to successfully address bias-based bullying: The case for promoting professional ethos - Gutzwiller-Helfenfinger, Eveline (Frontiers in Education, 2024)
This conceptual article proposes a contextualized view of teachers’ professional ethos in the area of school bullying in general and regarding bias-based bullying in particular. I argue that teachers need a contextualized or embedded professional ethos to successfully address bias-based bullying and promote positive social relationships among students. Three objectives relating to the improvement of educational practices in addressing school bullying, particularly bias-based bullying, are pursued. First, with a view to professionalizing teachers, this article attempts to make tangible the abstract concept of professional ethos, a concept largely neglected in contemporary teacher education. Secondly, the contribution synthesizes current knowledge on the phenomenon of bias-based bullying in schools and the role of teachers in the bullying dynamics, highlighting the link between empirical findings and pedagogical practice. Thirdly, I propose a contextualized model as a guide how teachers’ professional ethos in the area of bias-based bullying can be developed and fostered.